Myths of modernity : peonage and patriarchy in Nicaragua - Dore, Elizabeth (E-Duke books scholarly collection., 2006)
Combines Marxist and postmodern approaches to argue that patriarchy has provided the central organizing principle of Nicaraguan agrarian labor systems.